Patient-level costs in margin re-excision for breast-conserving surgery. Issue 4 (19th December 2018) - Grant, Y; Al-Khudairi, R; St John, E; Barschkett, M; Cunningham, D; Al-Mufti, R; Hogben, K; Thiruchelvam, P; Hadjiminas, D J; Darzi, A; Carter, A W; Leff, D R
Abstract: Background: High rates of reoperation following breast-conserving surgery (BCS) for positive margins are associated with costs to healthcare providers. The aim was to assess the quality of evidence on reported re-excision costs and compare the direct patient-level costs between patients undergoing successful BCS versus reoperations after BCS. Methods: The study used data from women who had BCS with or without reoperation at a single institution between April 2015 and March 2016. A systematic review of health economic analysis in BCS was conducted and scored using the Quality of Health Economic Studies (QHES) instrument. Financial data were retrieved using the Patient-Level Information and Costing Systems (PLICS) for patients. Exchange rates used were: US 1 = £0·75, £1 = €1·14 and US 1 = €0·85. Results: The median QHES score was 47 (i.q.r. 32·5–79). Only two of nine studies scored in the upper QHES quartile (score at least 75). Costs of initial lumpectomy and reoperation were in the range US 1234–11786 and 655–9136 respectively. Over a 12-month interval, 153 patients had definitive BCS and 59 patients underwent reoperation. The median cost of reoperations after BCS (59 patients) was £4511 (range 1752–18 019), representing an additional £2136 per patient compared with BCS without reoperation ( P < 0·001). Conclusion: The systematic review demonstrated variation in methodological approach to cost estimates and a paucity of high-quality cost estimate studies for reoperations. Extrapolating local PLICS data to a national level suggests that getting BCS right first time could result in substantial savings. Abstract : Reoperations expensive